Search for the rare decay KS -> mu+ mu- - collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2012)
A search for the decay KS -> mu+ mu- is performed, based on a data sample of 1.0 fb^-1 of pp collisions at \sqrt{s}=7 TeV collected by the LHCb experiment at the Large Hadron Collider. The observed number of candidates is consistent with the background-only hypothesis, yielding an upper limit of BR(KS -> mu+ mu-) < 11 (9) x 10^-9 at 95 (90)% confidence level. This limit is a factor of thirty below the previous measurement.